2021
DOI: 10.1109/jssc.2021.3080383
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Energy-Autonomous Temperature-to-Time Converter Powered by a Triboelectric Energy Harvester for Biomedical Applications

Abstract: This article presents a fully energy-autonomous temperature-to-time converter (TTC), entirely powered up by a triboelectric nanogenerator (TENG) for biomedical applications. Existing sensing systems either consume too much power to be sustained by energy harvesting or have poor accuracy. Also, the harvesting of low-frequency energy input has been challenging due to high reverse leakage of a rectifier. The proposed dynamic leakage suppression full-bridge rectifier (DLS-FBR) reduces the reverse leakage current b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Tan et al reported a fully energy-autonomous temperature-to-time converter (TTC) based on the TENG for biomedical applications. 93 The proposed TTC was attached to the arm to be driven by the low frequency (<1 Hz) of human arm motion. After the storage capacitor collected a voltage of 0.6 V, the low-power TTC, which performed one-shot conversion of temperature to pulse width, was activated by the power management unit.…”
Section: Harvesting Human Mechanical Energy With Tengs For Power Supplymentioning
confidence: 99%
“…Tan et al reported a fully energy-autonomous temperature-to-time converter (TTC) based on the TENG for biomedical applications. 93 The proposed TTC was attached to the arm to be driven by the low frequency (<1 Hz) of human arm motion. After the storage capacitor collected a voltage of 0.6 V, the low-power TTC, which performed one-shot conversion of temperature to pulse width, was activated by the power management unit.…”
Section: Harvesting Human Mechanical Energy With Tengs For Power Supplymentioning
confidence: 99%